Análise dos efeitos de programas educacionais: o caso projeto jovem de futuro do Instituto Unibanco - Silva, Samara Paladino Roriz e (2011)
Submitted by Cristiane Oliveira (cristiane.oliveira@fgv.br) on 2011-06-03T19:03:08Z No. of bitstreams: 1 66080100277.pdf: 512476 bytes, checksum: 24876c8e6745ffc883e662cf3ebe7213 (MD5) === Approved for entry into archive by Marcia Bacha(marcia.bacha@fgv.br) on 2011-06-06T17:31:08Z (GMT) No. of bitstreams: 1 66080100277.pdf: 512476 bytes, checksum: 24876c8e6745ffc883e662cf3ebe7213 (MD5) === Made available in DSpace on 2011-06-06T17:31:58Z (GMT). No. of bitstreams: 1 66080100277.pdf: 512476 bytes, checksum: 24876c8e6745ffc883e662cf3ebe7213 (MD5) Previous issue date: 2010-06-29 === One of Brazil´s greatest challenges today in relation to its system of education, is to improve the quality of teaching/education in public schools. This motivated the Unibanco Institute to create the Projeto Jovem de Futuro. The project offers State public schools at secondary school level, technical and financial support for the implementation of a plan to improve the quality in the dynamics of school procedures, with an aim to increasing the students output and to reducing the rate of dropouts. This work carries out an assessment of the Project´s first year in the States of Minas Gerais and Rio Grande do Sul. The concepts of statistical evaluation of social programmes are adopted to estimate the average effect of the Project on students’ marks, on the heterogeneous effects and on the dispersion effect of students’ marks. The results indicate that the Projeto Jovem de Futuro had a large impact on the average marks of students and contributed towards the reduction in the inequality of proficiency, in the schools that participated. In order to better understand what generated the increase in the proficiency of the students who participated in the programme, assessments were also carried out with an aim to identifying which type of investment, on average, contributed most to the development of the students. In this respect, it was impossible to reach a conclusive result. === Um dos maiores desafios atuais do Brasil em relação ao seu sistema educacional é a melhora da qualidade da educação oferecida pela rede pública de ensino. Motivado por isso, o Instituto Unibanco criou o Projeto Jovem de Futuro. O projeto oferece às escolas públicas estaduais de ensino médio apoio técnico e financeiro para a implantação de um plano de melhoria de qualidade na dinâmica de funcionamento escolar, com o objetivo de aumentar o rendimento dos alunos e diminuir os índices de evasão escolar. Este trabalho faz uma avaliação do primeiro ano do projeto nos estado de Minas Gerais e Rio Grande do Sul. Os conceitos de avaliação estatística de programas sociais são utilizados na estimação do efeito médio do projeto sobre as notas dos alunos, dos efeitos heterogêneos e do efeito na dispersão das notas dos alunos. Os resultados encontrados indicam que o Projeto Jovem de Futuro teve grande impacto sobre a nota média dos alunos e contribuiu para a redução da desigualdade nas notas dos alunos das escolas participantes. A fim de entender o que gerou o aumento da proficiência dos alunos participantes do programa, também são feitas algumas estimações com o objetivo de captar qual o tipo de investimento que, em média, contribuiu mais para o desenvolvimento dos alunos. Neste aspecto não foi possível chegar a um resultado conclusivo.